Humoral immune response of BBIBP COVID‐19 vaccination before and after the booster immunization. Issue 8 (16th March 2022) - Cheng, Zhangkai J.; Huang, Huimin; Zheng, Peiyan; Xue, Mingshan; Ma, Jing; Zhan, Zhiqing; Gan, Hui; Zeng, Yifeng; Lin, Runpei; Li, Shiyun; Zhong, Ruifen; Li, Siping; et al.
Abstract: Background: The inactivated Sinopharm/BBIBP COVID‐19 vaccine has been widely used in the world and has joined the COVAX vaccine supply program for developing countries. It is also well adapted for usage in low‐ and middle‐income nations due to their low storage requirements. Objective: This study aims to report on the kinetics, durability, and neutralizing ability of the induced immunity of the BBIBP vaccine, and the intensified antibody response elicited by the booster. Methods: A total of 353 healthy adult participants, aged 20–74 years, were recruited in this multicenter study. A standard dose of the BBIBP vaccine was administered (Month 0), followed by a second standard dose (Month 1), and a booster dose (after Month 7). Vaccine‐induced virus‐specific antibody levels (SARS‐CoV‐2‐IgA/IgM/IgG), conventional virus neutralization test (cVNT), pseudovirus neutralization test (pVNT), and surrogate virus neutralization test (sVNT) were monitored over multiple time points. Results: Neutralizing titers induced by the two doses of inactivated vaccine for COVID‐19 peaked at Month 2 and declined to 33.89% at Month 6. Following the booster dose, elevated levels of antibodies were induced for IgA, IgG, and neutralizing antibodies, with neutralizing titer reaching 13.2 times that of before the booster. Conclusion: By monitoring the antibody titer levels postvaccination, this study has shown that serum antibody levels will decrease over time, but a notable spike in antibody levels postbooster highlights the anamnestic immune response. This signifies that the protection capability has increased following the injection of booster immunization. Abstract : This study monitored specific antibody levels (IgA/IgM/IgG), cVNT, pVNT, and sVNT tests in 353 healthy adult subjects over the course of vaccination. The first two injections of the vaccine induce humoral responses with a peak at 2 months. Following the booster dose, IgA, IgG, and neutralizing antibodies increase with a neutralizing titer 13.2 times higher than before the booster.Abbreviations: cVNT, conventional virus neutralization test; Ig, immunoglobulin; pVNT, pseudo‐virus neutralization test; sVNT, surrogate virus neutralization test